Mission San Juan Bautista - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows an exterior view of Mission San Juan Bautista, including the roofed walkway/arcades. A bell hangs on a wooden stand in front of the building. The sign above the bell reads in part "El Camino Real."